Characterization of protein isolates from bullet tuna (Auxis rochei rochei) - Anuevo, Gwen M. (Miagao, Iloilo University of the Philippines in the Visayas, 2007)
Protein isolates were obtained from bullet tuna Auxis rochei rochei by extraction and precipitation techniques using acid (pH 3.15) or alkali (pH 10.00). Higher protein solubility was observed after 15 days of storage at 4 degrees centigrade both for acid and alkali treatments. Protein recovery showed no significant difference (P<0.05) between acid (61. percent) or alkali (59.7) treatments ., Gelling properties were not exhibited by ay of the protein isolates, but characterization in terms of proximate composition showed that protein islolate from bullet tuna is a good source of protein (76 percent - 45 percent, for acid and alkali protein isolates, respectively). The fatty acid profile of the isolates revealed also that bullet tuna is a good source of docosahexanoic acid (DHA). Hence, protein isolates from bullet tuna can be used as food additive to fortify or add value to the food product, and likewise to boost economic return of bullet tuna market.
Special Problem (Master of Science in Chemistry) -- Miagao, Iloilo : College of Arts and Sciences, University of the Philippines in the Visayas, April 2007
Keywords: Tuna, Bullet; Auxis rochei rochei